2019
DOI: 10.1103/physrevlett.123.116105
|View full text |Cite
|
Sign up to set email alerts
|

Topology of Disordered 3D Graphene Networks

Abstract: Disordered carbons comprise graphene fragments assembled into three-dimensional networks. It has long been debated whether these networks contain positive curvature, as seen in fullerenes, negative curvature, as proposed for the schwarzite structures, or zero curvature, as in ribbons. We present a meshbased approach to analyze the topology of a set of nanoporous and glassy carbon models that accurately reproduce experimental properties. Although all three topological elements are present, negatively curved str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 32 publications
0
55
0
Order By: Relevance
“…This combustion route to graphite unifies past literature models of graphitisation, which have been the subject of ongoing debate. While pentagons 35 and heptagons 36 have both been proposed as sources of positive and negative curvature, respectively, a key aspect of our mechanism is their arrangement in lines as proposed more recently [29][30][31][32][33][34] . The pentagon/heptagon chains can be understood as the (unspecified) cross-links proposed by Franklin, which locked nanocrystallites together 3 , while collapse of the structure is reminiscent of the "falling cards" model of Dahn et al 37 .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…This combustion route to graphite unifies past literature models of graphitisation, which have been the subject of ongoing debate. While pentagons 35 and heptagons 36 have both been proposed as sources of positive and negative curvature, respectively, a key aspect of our mechanism is their arrangement in lines as proposed more recently [29][30][31][32][33][34] . The pentagon/heptagon chains can be understood as the (unspecified) cross-links proposed by Franklin, which locked nanocrystallites together 3 , while collapse of the structure is reminiscent of the "falling cards" model of Dahn et al 37 .…”
Section: Discussionmentioning
confidence: 78%
“…This idea is consistent with studies of carbon nanohorns and nanotubes where oxidation occurs preferentially at pentagonal rings [23][24][25] and is exploited to access internal cavities by etching the tips [26][27][28] . Experimental and theoretical works [29][30][31][32][33][34] have shown that defects such as pentagons, heptagons and octagons are arranged in lines, forming extended defects. An example of a model of a porous carbon showing these extended defects is depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent study of amorphous 2D silica reveals that the distribution of silicon atoms possesses the remarkable property of DHU (45). In a wider context, amorphous carbon-based systems have been extensively studied, including graphene sheets (54)(55)(56), cross-linked graphene network (57), and amorphous glassy carbon and carbon fibers (58,59), to name a few.…”
Section: Significancementioning
confidence: 99%